Rute Terpendek Pengiriman Katering Makanan Menggunakan Geographic Information System dengan Metode Dijkstra - Adira, Muhammad Faris; Triase, Triase (Bulletin of Computer Science Research, 2026)
The problem of determining catering delivery routes at UMKM Vfoodia in Medan City is still carried out manually and relies heavily on couriers’ experience, which may lead to inefficiencies, especially in cases of courier replacement and limited delivery time windows. This condition results in delivery delays and difficulties for couriers in understanding customer locations and delivery sequences. This study aims to develop a catering delivery route determination system based on Geographic Information System (GIS) using the Dijkstra algorithm. The system is developed as a web-based application accessible via Android devices to support both administrative and courier activities. GIS is utilized to visualize customer locations and road networks on a digital map, while the Dijkstra algorithm is applied to compute the shortest route between two points. In daily delivery operations involving multiple destinations, the Dijkstra algorithm is executed repeatedly, where the destination point is updated each time a customer delivery is completed. The system is integrated with the OpenRouteService API to obtain distance and travel time estimations and is equipped with a caching mechanism to reduce repetitive API calls. The contribution of this research lies in the application of the standard Dijkstra algorithm in a repetitive manner within a GIS-based system to support structured multi-destination catering delivery at the UMKM scale. Experimental results show that the system is able to generate the shortest delivery route with a minimum distance of 6.0 km in the test scenario and helps make the delivery process more organized and easier for couriers to understand. Therefore, the proposed system improves delivery efficiency and enhances the quality of catering delivery services at UMKM Vfoodia.